PENGARUH PENGGUNAAN TEKNOLOGI STAR TELLER TERHADAP KUALITAS PELAYANAN DAN IMPLIKASI PADA KEPUASAN NASABAH PADA PT. BANK CENTRAL ASIA TBK, KCP MANGUNSARKORO CIANJUR - Trifena Lumbantoruan; Prihartono Aksan Halim (Media Bina Ilmiah, 2023)
As the development of technology is getting more advanced, the competition in banking services are also getting higher. The purpose of this study is to find how important the Star Teller machine in improving banking quality service and the impact on customer's satisfaction of BCA as the biggest private bank in Indonesia which always develops its technology especially the Star Teller machine. This study is using quantitative method which makes all the data in a form of number and being analyzed by collecting, clarifying the real situation which become the background of the conclusion. According to the table above, it can be concluded that BCA KCP Mangunsarkoro Cianjur is dominated by customer with the age of 21 year old for 17,8%, followed by customer with the age range of 21-30 year old which has bigger percentage than other two kinds of customer. The last one is customer with the age over 30 year old for 8%. BCA starts to improve its services quality. One of them is developing a machine called Star Teller. This machine is created to simplify services for customers. Beside, this machine helps the bankers to improve the efficiency of bank services.